Bringing Back the Joy: A Study of the Short Documentary Film The Last Repair Shop (2023) - Rudy (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
This literature research focuses on discussing the conceptualization of joy in American short documentary film entitled The Last Repair Shop (2023). As a feeling that everyone needs in life, the concept of joy needs to be studied. It is also expected that the study can become an additional reference for future research and contribute to increasing understanding of the concept of joy and enriching theory in literary and cultural studies. The study aims at identifying how joy is portrayed and conceptualized through the documentary film. The Primary data for qualitative research is in the form of a collection of statements from actors obtained from documentary short films. This study also utilizes Hall's representation theory to analyze statements from actors to construct the concept of joy portrayed in the documentary film. The results of data analysis and interpretation show that the concept of joy can refer to the power to change a person's life because it can be a source of change or a result obtained from change. In addition, joy as portrayed through the documentary can also beconceptualized as kindness towards oneself and others.